Affect and counter-conduct: cultivating action for social change in human rights education. Issue 4 (4th July 2018) - Zembylas, Michalinos
ABSTRACT: This paper explores the entanglement between two partially connected concerns that offer the potential to animate current discussions on human rights teaching and learning: 'affect' and 'counter-conduct'. Both terms are at the heart of human rights education (HRE) approaches that aim at cultivating resistance in children and youth so that they respond in critically affective and action-oriented ways to human rights violations and social injustices in 'the everyday'. These concepts are used to explore: first, how to encourage children and youth to enact forms of counter-conduct that are critical in human rights struggles, rather than responses which are sedimented through the governing technologies of declarational approaches of HRE; and second, how these counter-conduct practices may constitute ethical and political practices that critique liberal and sentimental forms of affect about human rights violations. It is argued that theoretical insights that pay attention to counter-conduct and affect offer possibilities for reconsidering normalized ideas in HRE.